Proceedings of the 2018 Conference of the North American Chapter Of the Association for Computational Linguistics: Hu 2018
DOI: 10.18653/v1/n18-1180
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Language Proficiency from Eye Movements in Reading

Abstract: We present a novel approach for determining learners' second language proficiency which utilizes behavioral traces of eye movements during reading. Our approach provides standalone eyetracking based English proficiency scores which reflect the extent to which the learner's gaze patterns in reading are similar to those of native English speakers. We show that our scores correlate strongly with standardized English proficiency tests. We also demonstrate that gaze information can be used to accurately predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Whitford and Titone (2012, 2016, 2017) who recorded eye movements of late L2 bilinguals of various ages (18–86 years), different language dominance (English or French), and proficiency found that the amount of exposure to the weaker language determined the magnitude of the frequency effect, with lower levels of exposure leading to larger frequency effects in early and late eye-movement measures in L2. Berzak, Katz and Levy (2018) recently demonstrated that the proficiency level in L2 could affect eye movements even more directly. They found that first fixation duration and total reading times not only correlated with standardized tests of English language proficiency ( MET : r = .5 and TOEFL : r = .54) but were also effective in predicting the outcomes of these tests.…”
Section: Introductionmentioning
confidence: 99%
“…Whitford and Titone (2012, 2016, 2017) who recorded eye movements of late L2 bilinguals of various ages (18–86 years), different language dominance (English or French), and proficiency found that the amount of exposure to the weaker language determined the magnitude of the frequency effect, with lower levels of exposure leading to larger frequency effects in early and late eye-movement measures in L2. Berzak, Katz and Levy (2018) recently demonstrated that the proficiency level in L2 could affect eye movements even more directly. They found that first fixation duration and total reading times not only correlated with standardized tests of English language proficiency ( MET : r = .5 and TOEFL : r = .54) but were also effective in predicting the outcomes of these tests.…”
Section: Introductionmentioning
confidence: 99%
“…A subset of CELER (CELER v1) was previously used in two studies, Berzak et al (2017) and Berzak et al (2018). Berzak et al (2017) used the L2 part of the data, and capitalized on the four native languages of the L2 participants in CELER v1 to demonstrate that the native language of L2 speakers can be decoded from eye-movement features during reading.…”
Section: Uses Of the Corpusmentioning
confidence: 99%
“…As outlined in Section 3.3, an effective approach for text simplification in assistive technology is to include the user in the decision of what is simplified. Prior research has shown that eye-tracking (Berzak et al, 2018) and scroll-based interactions (Gooding et al, 2021a) correlate with text understanding. As such, these implicit techniques can be used to gain an insight into what the reader is finding difficult.…”
Section: Privacy and Securitymentioning
confidence: 99%